Post-Operative Modified All-Inside ACL Reconstruction Technique's Clinical Outcomes and Isokinetic Strength Assessments - Genc, Ahmet Serhat; Guzel, Nizamettin; Yilmaz, Ali Kerim; Ermis, Egemen; Kurtca, Mine Pekesen; Agar, Anil; Kehribar, Lokman (Mdpi, 2023)
Background and Objective: Anterior cruciate ligament (ACL) injuries are very common among the athletic population. ACL reconstruction (ACLR) performed because of these injuries is one of the procedures performed by orthopedic surgeons using different grafting methods. This study aims to compare the data related to post-operative 6-month isokinetic strength values, strengthrelated asymmetry rates, time parameters, and joint angle in athletes who underwent ACLR with the Modified All-inside (4ST) technique, on both the healthy knee (HK) and the ACLR-applied sides. Materials and Methods: A total of 20 athletes from various sports on whom the 4ST ACLR technique had been applied by the same surgeon were evaluated retrospectively. Lysholm, Tegner, and International Knee Documentation Committee (IKDC) scores of the patients were obtained preoperative and at 6 months post-operative. Isokinetic knee extension (Ex) and flexion (Flx) strengths on the HK and ACLR sides of the patients were evaluated with a series of four different angular velocities (60, 180, 240, and 300(circle)/s). In addition to peak torque (PT) and hamstring/quadriceps ratio (H/Q) parameters, the findings were also evaluated with additional parameters such as joint angle at peak torque (JAPT), time to peak torque (TPT), reciprocal delay (RD), and endurance ratio (ER). Results: There was a significant improvement in the mean Lysholm, Tegner, and IKDC scores after surgery compared with pre-operative levels (p < 0.05). As for PT values, there were significant differences in favor of the HK in the 60, 180, and 300(circle)/s Ex phases (p < 0.05). In terms of the H/Q and (hamstring/hamstring)/(quadriceps/quadriceps) (HH/QQ) ratios, there were significant differences at 300(circle) /s (p < 0.05). In terms of JAPT, there were significant differences in the 300(circle)/s Ex and 180(circle)/s Flx phases (p < 0.05). In terms of TPT, there were significant differences in the 300ffi /s Ex phase (p < 0.05). In terms of RD and ER, no significant difference was observed between the HK and ACLR sides at any angular velocity. Conclusions: Although differences were observed in PT values, particularly in the Ex phase, this did not cause a significant change in H/Q ratios. Similar results were observed for additional parameters such as JAPT, TPT, RD, and ER. The results show that this ACLR technique can be used in athletes in view of strength gain and a return to sports.
Keywords: anterior cruciate ligament reconstruction; return to sports; isokinetic evaluations; modified all-inside; knee strength; knee scores; surgical side